2006
DOI: 10.1007/s00280-006-0196-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of N-2-chloroethylaziridine, a volatile cytotoxic metabolite of cyclophosphamide, in the rat

Abstract: For the first time, CEA was demonstrated to be an important in vivo metabolite of CP in the present study. In light of the poor permeability and in vivo stability of PM, the ultimate DNA alkylator, the findings obtained in this study suggested that CEA may contribute significantly to the overall antitumor activity of prodrug CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For 5-FU, epirubicin and cyclophosphamide (and its metabolite), the unbound fraction (fu) is moderate or high (0.2-0.9) and no major species differences have been demonstrated [31][32][33][34][35][36][37]. Therefore the fu ratio f u rat =f u human ð Þwas in the scaling set to 1 for these drugs.…”
Section: Scalingmentioning
confidence: 99%
“…For 5-FU, epirubicin and cyclophosphamide (and its metabolite), the unbound fraction (fu) is moderate or high (0.2-0.9) and no major species differences have been demonstrated [31][32][33][34][35][36][37]. Therefore the fu ratio f u rat =f u human ð Þwas in the scaling set to 1 for these drugs.…”
Section: Scalingmentioning
confidence: 99%
“…Although the generation of CEZ has been demonstrated both in vivo and in vitro , determining the relative contribution of CEZ to CPA-induced cytotoxicity has proven difficult due to the compound’s volatility and the instability of its precursor, PM. CEZ plasma concentrations were shown to peak 5 minutes after intravenous PM administration in rats (Lu and Chan, 2006). An additional study demonstrated that following complete degradation of PM in solution, 85% of the solution’s cytotoxicity remained due to the generation and continued presence of CEZ (Chan et al , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, PM can undergo another spontaneous reaction to form the volatile, cytotoxic metabolite chloroethylaziridine (CEZ) , which, due to its higher cell permeability (Hata and Watanabe, 1994) and longer half-life compared to PM (Lu and Chan, 2006), may also contribute to CPA-induced ovotoxicity .…”
Section: Published In the Book Ovarian Toxicology As A Subsection Of mentioning
confidence: 99%
“…Although the generation of CEZ has been demonstrated both in vivo and in vitro, determining the relative contribution of CEZ to CPAinduced cytotoxicity has proven difficult due to the compound's volatility and the instability of its precursor, PM. CEZ plasma concentrations were shown to peak 5 minutes after intravenous PM administration in rats (Lu and Chan, 2006). An additional study demonstrated that following complete degradation of PM in solution, 85% of the solution's cytotoxicity remained due to the generation and continued presence of CEZ (Chan et al, 1994).…”
Section: Birth Puberty Menopausementioning
confidence: 99%